Comparison of real world and core laboratory lupus anticoagulant results from the Antiphospholipid Syndrome Alliance for Clinical Trials and International Networking (APS ACTION) clinical database and repository. (8th September 2019) - Efthymiou, Maria; Mackie, Ian J.; Lane, Philip J.; Andrade, Danieli; Willis, Rohan; Erkan, Doruk; Sciascia, Savino; Krillis, Steven; Bison, Elisa; Borges Galhardo Vendramini, Margarete; Romay‐Penabad, Zurina; Qi, Miao; et al.
Abstract: Background: Variability remains a challenge in lupus anticoagulant (LA) testing. Objective: To validate LA test performance between Antiphospholipid Syndrome Alliance for Clinical Trials and International Networking (APS ACTION) Core laboratories and examine agreement in LA status between Core and local/hospital laboratories contributing patients to this prospective registry. Methods: Five Core laboratories used the same reagents, analyzer type, protocols, and characterized samples for LA validation. Non‐anticoagulated registry samples were retested at the corresponding regional Core laboratories and anticoagulated samples at a single Core laboratory. Categorical agreement and discrepancies in LA status between Core and local/hospital laboratories were analyzed. Results: Clotting times for the reference/characterized plasmas used for normalized ratios were similar between Core laboratories (CV <4%); precision and agreement for LA positive/negative plasma were similar (all CV ≤5%) in the four laboratories that completed both parts of the validation exercise; 418 registry samples underwent LA testing. Agreement for LA positive/negative status between Core and local/hospital laboratories was observed in 87% (115/132) non‐anticoagulated and 77% (183/237) anticoagulated samples. However, 28.7% (120/418) of samples showed discordance between the Core and local/hospital laboratories or equivocal LA results. Some of the results of the local/hospital laboratories might have been unreliable in 24.7% (41/166) and 23% (58/252) of the total non‐anticoagulated and anticoagulated samples, respectively. Equivocal results by the Core laboratory might have also contributed to discordance. Conclusions: Laboratories can achieve good agreement in LA performance by use of the same reagents, analyzer type, and protocols. The standardized Core laboratory results underpin accurate interpretation of APS ACTION clinical data.